Living with reduced income: An analysis of household financial vulnerability under COVID-19 - Catarina Mid\~oes; Mateo Seré (University of Essex, Institute for Social and Economic Research (ISER), 2020)
The COVID-19 crisis has led to substantial reductions in earnings. We propose a new measure of financial vulnerability, computable through survey data, to determine whether households can withstand a certain income shock for a defined period of time. Using data from the ECB Household Finance and Consumption Survey (HFCS) we analyse preexisting financial vulnerability in seven EU countries. We find that income support is essential for many families: 47.2 million individuals, out of the 243 million considered, cannot afford three months of food and housing expenses without privately earned income. Differences across countries are stark, and those born outside of the EU are especially vulnerable. Through a tax-benefit microsimulation exercise, we then derive household net income when employees are laid-off and awarded the COVID-19 employment protection benefits enacted in the different countries. Our findings suggest that the COVID-19 employment protection schemes awarded are extremely effective in reducing the number of vulnerable individuals. The relative importance of rent and mortgage suspensions in alleviating vulnerability is highly country dependent.
Keywords: D14; E27; J65; 330; vulnerability; household finance; microsimulation; COVID-19